2009
DOI: 10.1016/j.febslet.2009.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Methylene blue and dimebon inhibit aggregation of TDP‐43 in cellular models

Abstract: a b s t r a c tAmyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration with ubiquitinated inclusions (FTLD-U) are major neurodegenerative diseases with TDP-43 pathology. Here we investigated the effects of methylene blue (MB) and dimebon, two compounds that have been reported to be beneficial in phase II clinical trials of Alzheimer's disease (AD), on the formation of TDP-43 aggregates in SH-SY5Y cells. Following treatment with 0.05 lM MB or 5 lM dimebon, the number of TDP-43 aggregates was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 38 publications
1
72
0
2
Order By: Relevance
“…Our experiments demonstrated that although these four compounds function within the UPR ER they operate through different branches of this pathway to achieve neuroprotection. There is growing evidence for a protective role of methylene blue against multiple forms of neurodegeneration including mTDP-43 Yamashita et al, 2009), mFUS , mutant SOD1 (Dibaj et al, 2012) mutant polyglutamine proteins (Sontag et al, 2012), and MB has shown promising effects in a Phase II clinical trial for AD (Gura, 2008). MB is not protective in adult SOD1 (Lougheed and Turnbull, 2011) or TDP-43 mice (Audet et al, 2012) and we found diminished effect on worms , and no activity in zebrafish (data not shown) after the phenotypes have been established, indicating that these compounds may not be useful for treating the disorder.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our experiments demonstrated that although these four compounds function within the UPR ER they operate through different branches of this pathway to achieve neuroprotection. There is growing evidence for a protective role of methylene blue against multiple forms of neurodegeneration including mTDP-43 Yamashita et al, 2009), mFUS , mutant SOD1 (Dibaj et al, 2012) mutant polyglutamine proteins (Sontag et al, 2012), and MB has shown promising effects in a Phase II clinical trial for AD (Gura, 2008). MB is not protective in adult SOD1 (Lougheed and Turnbull, 2011) or TDP-43 mice (Audet et al, 2012) and we found diminished effect on worms , and no activity in zebrafish (data not shown) after the phenotypes have been established, indicating that these compounds may not be useful for treating the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it was demonstrated that MB can inhibit aggregate formation of a variety of proteins (Wischik et al, 1996; Taniguchi et al, 2005;Yamashita et al, 2009). To verify this hypothesis in SOD1 G93A mice, we compared the ratio of soluble versus insoluble fractions of SOD1 in the spinal cord of SOD1 G93A mice, treated or not (Fig.…”
Section: Accumulation Of Insoluble Sod1 Is Not Diminished By Mb Treatmentioning
confidence: 93%
See 1 more Smart Citation
“…[26] In rTg4510 tau-transgenic mice, MTC prevented behavioral deficits and reduced soluble brain tau levels when given before formation of NFTs in the brain, [25] but one study suggested that it could not be able to reverse established NFT pathology. [31] Other studies reported inhibitory activities of MTC on aggregation processes of prion protein, [32] α-synuclein, transactive response DNA-binding protein 43, [33,34] and huntingtin [35] …”
Section: Tais For the Treatment Of Ad: Preclinical Studies Of Methyltmentioning
confidence: 99%
“…процесс патологической агрегации белков, и все этапы этого процесса рассматриваются как потенциальные мишени для разработки новых терапевтических средств, исключительную важность приобретает описанное недавно свойство димебона влиять на формирование и/или стабильность патогенных белковых агрегатов [20,21]. Однако остается неясным, действует ли димебон непосредственно на процесс белковой агрегации или же его эффект связан с активацией процессов разрушения уже сформированных белковых фибриллярных структур, также неясно, какие именно молекулярные механизмы ответственны за антиагрегационные свойства димебона.…”
unclassified